The Energy of Russia - Veli-Pekka Tynkkynen (Edward Elgar Publishing, 2019)
This timely book analyses the status of hydrocarbon energy in Russia as both a saleable commodity and as a source of societal and political power. Through empirical studies in domestic and foreign policy contexts, Veli-Pekka Tykkynen explores the development of a hydrocarbon culture in Russia and the impact this has on its politics, identity and approach to climate change and renewable energy.